ANALISIS KEMAMPUAN KEUANGAN DAERAH PEMERINTAH KABUPATEN JAYAPURA - La Ode Abdul Wahab (Sekolah Tinggi Ilmu Ekonomi Port Numbay Jayapura, 2017)
The purpose of this paper is to analyze and obtain empirical evidence about the regional financial performance and capability of Jayapura Regency in the 2010-2014 fiscal year. The data analysis method used is the ratio of regional independence, regional dependency ratio, fiscal decentralization ratio, effectiveness ratio and regional financial efficiency ratio. The results obtained from this study are that the regional financial capacity of Jayapura Regency, measured from the level of regional independence in the 2010-2014 fiscal year, is included in the very low criteria, and the regional dependence level in that period is included in the very high criteria with the criteria of an instructive relationship pattern. The ratio of fiscal decentralization is still very low, the level of effectiveness of Regional Original Revenue in 2010-2014 is classified in the very effective category with a very efficient ratio of the collection of Regional Original Revenue. The regional financial capacity of Jayapura Regency in this case the level of regional independence and dependence as well as the level of fiscal decentralization is considered good if the Jayapura Regency government has been able to increase the percentage of Regional Original Revenue to above 40% of the balancing fund.